USM TRIUMPHS IN PUBLIC UNIVERSITIES' MATHEMATICS OLYMPIAD (OMUA) 2016 - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 20 December 2016 The Universiti Sains Malaysia (USM) School of Mathematical Sciences (PPSM) team emerged champions in the finals of the Public Universities' Mathematics Olympiad 2016, held at Universiti Putra Malaysia (UPM).